PEDICLED TRAPEZIUS MUSCULOCUTANEOUS FLAP IN THE RECONSTRUCTION OF A SHOULDER DEFECT AFTER THE RESECTION OF SOFT TISSUE SARCOMA – CASE REPORT AND LITERATURE REVIEW - Petrović, Bojan; Rajkovic, Stanislav; Bogosavljevic, Nikola; Stajic, Milan; Miceta, Lazar (Srpski medicinski časopis Lekarske komore, 2024)
Introduction: Soft tissue sarcomas (STS) in the extremities require complex treatment involving limb-sparing surgery with adjuvant therapy. The treatment involves tumor resection with wide margins along with additional radiation and/or chemotherapy. In addition to tumor resection, an important aspect is the reconstruction of the resulting soft tissue defect. For extensive reconstructive procedures in the upper extremities, literature suggests the use of free or pedicled flaps. In the shoulder region, due to its complex regional anatomy, selecting an appropriate flap is the surgical imperative. Recently, there has been significant interest in the use of the pedicled trapezius musculocutaneous flap, which offers certain advantages over other flaps.Case report: A female patient (31 years old) with STS in the left shoulder region, was surgically treated three times. The first surgery involved an intralesional procedure – R2 resection when a pleomorphic dermal sarcoma was diagnosed. After five months, a recurrence of the disease was detected based on magnetic resonance imaging (MRI) findings at the site of the surgical scar. Tumor resection was performed, and the soft tissue defect was covered with a free Thiersch partial-thickness skin graft. Histopathological analysis revealed a high-grade leiomyosarcoma. Two months after the second surgery, MRI findings confirmed a recurrence of the disease. Wide tumor resection was conducted, and the soft tissue defect was covered with a pedicled lower trapezius musculocutaneous flap.Conclusion: The literature lacks studies describing the outcomes of the use of trapezius flaps in the reconstruction of defects in the shoulder region following STS resection. Additionally, there is no unanimous official opinion on the resection margin width that is considered safe. The treatment outcome of our patient indicates the significant potential and advantages of the trapezius flap, as compared to other flaps of that region.
Keywords: leiomyosarcoma; tumor resection; resection margins; reconstructive surgery